Hyperphosphatemia-a predictor of poor prognosis among patients with sepsis or septic shock - A., Rakshith; C., Yogitha; S., Basanth Kumar (International Journal of Research in Medical Sciences, 2023)
Background: Sepsis is a life-threatening organ dysfunction resulting from dysregulated host responses to infection. Serum phosphorus level was closely related to the occurrence and prognosis of kidney disease and cardiovascular disease. It is of vital importance to re-evaluate the association between serum Phosphorus level and mortality in patients with sepsis and different septic subgroups. This study aims to examine the association of serum phosphorous levels with clinical outcomes among patients with sepsis. Methods: This study included 100 cases and was conducted at KIMS hospital Bangalore. Patients were included in the study as per inclusion criteria. SOFA scoring and APACHE-II scoring was done on first day of admission and serum phosphorus levels were sent. Patients were categorised according to phosphorous levels normal range (2.5-4.5mg/dl). Patients were followed up till primary and secondary outcome. Results: Of the 100 patients in this study 53 patients had normophosphatemia, 17 patients had hypophosphatemia, 30 patients had hyperphosphatemia. Comparison of mean APACHE-II scores, mean length of ICU stay (in days), mean length of hospital stay (in days), serum creatinine levels, between 3 groups was statistically significant. Conclusions: Hyperphosphatemia on first ICU admission day indicates poor clinical outcome among patients with sepsis or septic shock. Therefore, when patients are on ICU admission and under treatment, clinicians should pay more attention to the change of serum phosphate.